2021
DOI: 10.1021/acscatal.1c03579
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Intricate Mechanism and Selectivity of Syngas Conversion on Reduced ZnCr2Ox: A Quantitative Study from DFT and Microkinetic Simulations

Abstract: By combining reduced oxide and zeolite (e.g., ZnCrO x /MSAPO), bifunctional catalysts achieve outstanding olefin selectivity for syngas conversion via a relay process (CO + H2 → IM → olefin) and are one of the hottest catalytic systems. However, the reaction mechanism on the reduced ZnCrO x as well as the intermediate (IM = ketene versus methanol) entering the zeolite are under heated debate owing to the complexity of this system. Herein, we perform systematic density functional theory (DFT) calculations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…8a ). It indicates that the reaction equilibrium is successfully shifted and the reaction channel from intermediates to light olefins is opened up in the presence of SAPO-34, consistent with a recent theoretical study 21 . Thus, it forms a tandem catalytic process.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…8a ). It indicates that the reaction equilibrium is successfully shifted and the reaction channel from intermediates to light olefins is opened up in the presence of SAPO-34, consistent with a recent theoretical study 21 . Thus, it forms a tandem catalytic process.…”
Section: Resultssupporting
confidence: 89%
“…The above results demonstrate that the presence of coordination unsaturated Ga 3+ together with oxygen vacancies and zinc vacancies lead to a much more active ZnGaO x spinel in generating ketene-acetate (acetyl) intermediates. Interestingly, Lai et al recently also revealed the essential role of coordination unsaturated Cr 3+ together with the oxygen vacancies in the cleavage of the C–O bond over the highly reduced ZnCr 2 O 4 (110) surface 21 . Thus, incorporation of SAPO-34 would direct the reaction pathway towards light olefins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different from transition-metal catalysts, the bifunctional OX-ZEO catalysts separate the activation of syngas on the oxide part from the subsequent carbon chain growth and hydrogenation on the zeolite part. For the oxide part, the metal–oxide mixtures and/or complex metal oxides were found to be more active than the separated metal oxides. Identification of the active sites and their role in syngas conversion remain challenging. Mechanistic investigation and gaining an understanding of the intrinsic activity of prototype oxides such as ZnO and Cr 2 O 3 for syngas activation and the influence of the defects such as heterometal atoms are valuable for understanding the mechanism behind this phenomenon but not well explored yet.…”
Section: Introductionmentioning
confidence: 99%
“…With the raising amount of Ce 3+ dopant on catalyst surface, the electron transferring from Zn, Cr, and O to Ce was stimulated, which led to decreased electron density of surrounding metal ions, and obvious higher binding energy of Zn over 2.5‐Ce/ZC catalyst. This preferable electronic structure may facilitate the adsorption of electron‐rich intermediates (formate or bicarbonate species) [20] …”
Section: Resultsmentioning
confidence: 99%
“…This preferable electronic structure may facilitate the adsorption of electron-rich intermediates (formate or bicarbonate species). [20]…”
Section: Catalystmentioning
confidence: 99%